Respuestas

2012-10-11T07:24:45+02:00

1- 7a - 9b + 6a - 4b

     7a + 6a = 13 a

     -9b -4b = 13b                        R//  13a-13b

 

2- a + b -c -b -c +2c -a

      a -a= 0

     b - b= 0

     -c-c+2c= 0                              R// 0

 

3- 5x -11y -9 +20x -1 -y

    5x +20x= 25x

    -11y - y= -12y

      -9 -1= -10                               R// 25x - 12y -10

 

4- -6m + 8n +5 -m -n -6m -11

      -6m-m-6m = -13m

       8n -n = 7n

      5 -11= -6                                  R// -13m+7n-6

 

 

5- a+b +2b -2c +3a +2c -3b

   a + 3a= 4a

    b + 2b= 3b -3b= 0

     -2c + 2c = 0                                  R// 4a